Urban Internet myths and Realities: A Detroit case study. Issue 13 (9th November 2020) - Fernandez, Laleah; Reisdorf, Bianca C.; Dutton, William H.
ABSTRACT: This study challenges conventional expectations around Internet access and use in distressed urban neighbourhoods in the United States. Based on the findings of a survey of 525 Detroit, Michigan, residents, this study suggests that Detroit communities are more interested and more instrumental in their use of the Internet than suggested by characterizations of residents in low-income urban neighbourhoods being less engaged in the digital world. In countering these myths, our data provide a more realistic assessment of digital divides in Detroit, namely a divide between those with an Internet Service Provider (ISP) contract and those who are overly dependent on mobile, which has limited valuable uses of the Internet. Attitudes about the value of the Internet and concerns about costs have shaped ISP subscriptions and an overreliance on mobile phones. Those without home access and those more reliance on mobile phones engage in fewer online activities, such as health information seeking, fact finding, and shopping. This case study identifies key attitudes and barriers to access and use of ISPs in Detroit, which could be relevant to other distressed urban communities.